The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/anie.201404191
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Total Synthesis of Sespenine

Abstract: The first total synthesis of sespenine, a rare indole sesquiterpenoid from a mangrove endophyte, has been accomplished. A bioinspired aza-Prins/Friedel-Crafts/retro Friedel-Crafts cascade reaction assembles the bridged tetrahydroquinoline core. Further investigations on the aza-Prins cyclization imply that the C3 configuration of the hydroxyindolenine intermediate is crucial to the biosynthesis of sespenine and its congener xiamycin A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 60 publications
0
40
0
2
Order By: Relevance
“…Recently, we accomplished the total syntheses of a series of naturally occurring indole terpenoids (Scheme A) . From a retrosynthetic point of view, indole terpenoid scaffolds can be disassembled into indole (highlighted in red, Scheme A) and terpenoid (highlighted in blue, Scheme A) motifs in general ,,. Thus, structurally diverse indole terpenoid mimics can be directly prepared from simple indole and terpenoid building blocks (Scheme B), if efficient cross‐coupling‐type reactions are available for forming the linkage bonds (highlighted in cyan, Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we accomplished the total syntheses of a series of naturally occurring indole terpenoids (Scheme A) . From a retrosynthetic point of view, indole terpenoid scaffolds can be disassembled into indole (highlighted in red, Scheme A) and terpenoid (highlighted in blue, Scheme A) motifs in general ,,. Thus, structurally diverse indole terpenoid mimics can be directly prepared from simple indole and terpenoid building blocks (Scheme B), if efficient cross‐coupling‐type reactions are available for forming the linkage bonds (highlighted in cyan, Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…This was achieved by preparing the acetyl derivatives (acetyl-102 a/b) followed by HPLC purification. [84] synthetic organic chemistry can be an important tool to elucidate biosynthetic pathways, even up to intricate stereochemical details. Only the acetyl-102 a epimer was smoothly converted into the sespenine-like rearrangement product 104.…”
Section: Oxidative Cyclizations Of Indoloterpenoidsmentioning
confidence: 99%
“…This consideration was recently successfully employed for the first total synthesis of sespenine (Scheme 26 A). [84] Initial attempts with various oxidizing agents showed that strictly biomimetic conditions only gave low yields of sespenine (< 21 %), because the lack of a C2 substituent in indole promoting oxidative cleavage of the pyrrole ring. As a consequence of their convergent synthesis route, this problem could easily be solved by using methoxycarbonylsubstituted indole derivative 101, which was obtained in 12 steps.…”
Section: Oxidative Cyclizations Of Indoloterpenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Im Falle des Sespenins ( 50 ) handelt es sich beim Nukleophil für die oxidative Cyclisierung um die terminale Doppelbindung der Sesquiterpengruppe – formal eine Aza‐Prins‐Reaktion. Diese Überlegung wurde kürzlich für die erste Totalsynthese von Sespenin angewendet (Schema ) 84. Erste Versuche mit verschiedenen Oxidationsmitteln zeigten, dass strikt biomimetische Bedingungen nur zu niedrigen Ausbeuten an Sespenin (<21 %) führten, da das Fehlen eines Substituenten an C2 des Indols die oxidative Spaltung des Pyrrolringes begünstigte.…”
Section: Neue Biomimetische Syntheseansätzeunclassified